The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3892/etm.2019.7555
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‑derived exosomal miR‑183 associates with protein kinase activity and may serve as a novel predictive biomarker of myocardial ischemic injury

Abstract: Myocardial infarction (MI) is primarily caused by ischemic heart or coronary artery disease and is a major cause of mortality worldwide. Thus, it is necessary to establish reliable biochemical markers for the early diagnosis of MI. MicroRNAs (miRNAs or miR) have been demonstrated to circulate in biological fluids and are enclosed in extracellular vesicles, including exosomes. The current study assessed the differential expression of exosomal miRNAs in the plasma of patients with MI and healthy individuals, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Levels of miR-1915-3p, miR-4507, and miR-3656 in serum EVs are significantly lower in patients who have suffered acute myocardial infarction than in controls, suggesting that those RNAs may help predict such events, which are a major cause of mortality worldwide [ 144 ]. MicroRNAs in EVs may also serve as biomarkers of cardiovascular diseases, such as exosomal miR-183 for predicting myocardial infarction [ 145 ].…”
Section: Diagnosis Of Disease Based On Analysis Of Evs In Liquid Bmentioning
confidence: 99%
“…Levels of miR-1915-3p, miR-4507, and miR-3656 in serum EVs are significantly lower in patients who have suffered acute myocardial infarction than in controls, suggesting that those RNAs may help predict such events, which are a major cause of mortality worldwide [ 144 ]. MicroRNAs in EVs may also serve as biomarkers of cardiovascular diseases, such as exosomal miR-183 for predicting myocardial infarction [ 145 ].…”
Section: Diagnosis Of Disease Based On Analysis Of Evs In Liquid Bmentioning
confidence: 99%
“…The main cause of myocardial ischemia is coronary artery disease (CAD) due to atherosclerosis. However, microvascular disease associated with conditions such as diabetes mellitus can result in myocardial fibrosis and lead to heart failure [2]. Patients with CAD may undergo cardiac ischemic events that result in sudden death [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial ischemia is an acute and severe pathological condition, which leads to serious damage to the morphology, function, and metabolism of cardiomyocytes [ 1 , 2 ]. Emerging evidence has demonstrated that myocardial ischemia mediates the progression of multiple cardiovascular diseases, such as coronary artery disease, heart failure, and myocardial fibrosis, and contributes to high morbidity and mortality [ 3 , 4 ]. Moreover, ischemic heart disease has been identified as the leading cause of human death worldwide, and a threat to public health and imposed great economic burden on families and society [ 5 ].…”
Section: Introductionmentioning
confidence: 99%